2022
DOI: 10.1155/2022/2368323
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Ultrasonic Stimulation Performance on Permeability Enhancement in Coal Seam: Field Tests and In Situ Permeability Evaluation

Abstract: Power ultrasonic-assisted reservoir modification is a promising technique for enhanced coalbed methane recovery. However, the in-site performance of ultrasound-assisted CBM production has not yet been revealed. In the current study, the in situ antireflection test was conducted with high-power ultrasound ~18 kW in underground coal seam, and the antireflection performance was investigated by measuring the borehole drainage gas data in the field test zone, and then, the in situ permeability change of the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Jiang et al 17 found that the desorption rate of methane in coal was significantly accelerated when ultrasonic waves were propagated in the coal body. Furthermore, Fei et al 18 conducted an ultrasonic wave-based field application at the Shuanglong coal mine in Shaanxi, China, and showed that the average gas flowrate in a single hole increased from 20 to 106%; the coalbed permeability increased at least 2.36 times after ultrasonic stimulation. Based on experimental results and actual measurement data of mines, it is feasible that ultrasonic waves can promote CBM recovery by heat injection.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al 17 found that the desorption rate of methane in coal was significantly accelerated when ultrasonic waves were propagated in the coal body. Furthermore, Fei et al 18 conducted an ultrasonic wave-based field application at the Shuanglong coal mine in Shaanxi, China, and showed that the average gas flowrate in a single hole increased from 20 to 106%; the coalbed permeability increased at least 2.36 times after ultrasonic stimulation. Based on experimental results and actual measurement data of mines, it is feasible that ultrasonic waves can promote CBM recovery by heat injection.…”
Section: Introductionmentioning
confidence: 99%